2023
DOI: 10.1186/s12888-023-05399-z
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of post traumatic stress disorder and their relationship with the fear of COVID−19 and COVID−19 burden among health care workers after the full liberalization of COVID−19 prevention and control policy in China: a cross-sectional study

Huan Liu,
Ningying Zhou,
Zhiqing Zhou
et al.

Abstract: Background Over the past three years, the COVID-19 pandemic has brought an overwhelming impact on China’s hospital system and health care workers, which can lead to post traumatic stress disorder (PTSD) symptoms. Previous research has shown that the COVID-19 pandemic had long-term adverse effects on the mental health of health care workers. Indeed, PTSD symptoms have emerged as one of the significant mental health issues for health care workers arising from the COVID-19 pandemic. Therefore, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Compared with students who did not report contact with COVID-19 positive patients, the panic over COVID-19 may have increased the psychological burden on these individuals. Liu et al also found that the greater the fear of COVID-19, the higher the PTSD symptom score ( Liu et al, 2023 ). Interestingly, the current study found that maternal and paternal closeness were protective factors for depression and PTSD, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with students who did not report contact with COVID-19 positive patients, the panic over COVID-19 may have increased the psychological burden on these individuals. Liu et al also found that the greater the fear of COVID-19, the higher the PTSD symptom score ( Liu et al, 2023 ). Interestingly, the current study found that maternal and paternal closeness were protective factors for depression and PTSD, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, frontline nursing staff have been caring for infected patients, making them more vulnerable to the psychological consequences. Studies have found that health care workers caring for COVID-19 patients were at higher risk of insomnia symptoms ( 39 , 40 ), burnout, and post-traumatic stress disorder (PTSD) ( 27 ) due to excessive work pressure. Among all healthcare professionals, frontline nursing staff are particularly susceptible to sleep disorders during the COVID-19 pandemic ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The scale ( 27 ) consists of 5-items to assess PTSD experienced in the past month. Questions include “Have you ever had nightmares related to COVID-19 or have uncontrollable thoughts about COVID-19”?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus-19 fear increases with a higher score. A cut-off score of 21 and above has been proposed to differentiate the severity of fears associated with COVID-19 (22).…”
Section: The Fear Of Covid-19mentioning
confidence: 99%